Rasulullah Saw. dan Pencegahan Wabah Covid-19: Studi Tematik Hadis-hadis Penyakit Menular - Dede Mardiana (Faculty of Ushuluddin UIN Sunan Gunung Djati Bandung, 2021)
This research was motivated by the outbreak of Covid-19 that occurred in various parts of the world, including Indonesia. This study aims to discuss the practice of the Prophet Muhammad according to the hadith regarding disease outbreaks regarding the prevention of the Covid-19 pandemic. This research is a qualitative research through literature study using the syarah hadith method with a thematic approach. The results and discussion of this research show that the practice of the Prophet Muhammad according to the hadith themes of disease outbreaks after sharah, including social infections, quarantine for the infected, and taking treatment as a preventive and cure, where this is a practice applied in the prevention of the Covid-19 pandemic in the modern era. This study concludes that the Prophet's practice with regard to the prevention of infectious diseases according to syarah has been implemented as the most effective step to break the chain of the spread of the Covid-19 infectious disease that is happening in various parts of the world including Indonesia.